Imaginary Units of Publication Activities in Consumer Society - N. G. Bagdasaryan; L. A. Sonina (Moscow Polytechnic University, 2020)
Consumer society is associated with abundance of goods and services. Usually the scientific activity is not among them. Meanwhile, with scientometric indicators introduction, science activity acquired characteristics of consumer society in which it runs. The publication activity in modern circumstances got in track of consumer focus: authors, journals and mediators became economical actors, and scientific text became the product of "sings absorption and absorbed by signs". Was it possible to avoid it? - this question is without answer. It is clear that imposing quantitative scientometric indicators became the catalyst of this process.